Production of Particleboard from Lemongrass Leaves and Rice Straws - Khempila, Jarunee; Namprai, Chayanis; Kaewsai, Alisa (Journal of Advanced Development in Engineering and Science, 2023)
The aim of this research was to study the particleboard production from lemongrass leaves and rice straw. They were produced in the following proportions: 100% lemongrass leaves; 50% lemongrass leaves and 50% rice straw; and 100% rice straw. Also, the physical-mechanical properties of particleboards were assessed. For production of particleboard, pMDI was used as binder at 7% based on the dry weight. The press conditions and production plan of particleboards were as follows; 120°C pressing temperature, 147 bar pressure, and 5 min of pressing time. The particleboards were produced at 400-900 kg/m3 density and 450 mm × 450 mm × 10 mm dimension. In order to characterize the manufactured particleboards, their physical (density; moisture content; water absorption and thickness swelling) and mechanical properties (modulus of rupture and modulus of elasticity) were assessed and performed according to Thai Industrial Standard (TIS 876-2547) standards. The results showed that, the panel was odorless and colorless of burning, smooth surface, not bent or twisted shape and not noticed a cluster of material. Physical properties were determined average density, moisture content, water absorption, thickness swelling and has met the requirements of standards. Also, mechanical properties were determined average modulus of rupture and modulus of elasticity and has met the minimum requirements of standards, except with the proportion of 100% rice straw. Thus, the results of the study demonstrate that lemongrass leaves and lemongrass leaves with rice straw can be an alternative raw material source for particleboard industry.